Impact of Implementing All-Sky Radiance Assimilation for FY-3E MWHS-2 in the CMA-GFS - Li, Zeting; Han, Wei (Monthly weather review, 2025)
The Fengyun-3E ( FY-3E ) satellite was successfully launched into an early morning orbit on 5 July 2021, carrying a Microwave Humidity Sounder-2 (MWHS-2) to provide vertical profiles of atmospheric temperature and humidity. In this study, the all-sky FY-3E MWHS-2 radiances are effectively assimilated in the four-dimensional variational data assimilation (4DVar) system of the China Meteorological Administration Global Forecast System (CMA-GFS) to improve the global analysis and forecast. Before the all-sky radiance assimilation, several procedures were developed in the aspects of land emissivity retrieval, observation error modeling, and quality control based on the instrumental characteristics of MWHS-2. The results of 1-month cycle assimilation experiments indicate that the all-sky assimilation of MWHS-2 radiances considerably improved the initial conditions of temperature, humidity, and wind, and reduced the bias of stratocumulus clouds over the easternmost parts of the Maritime Continent. Regarding the geopotential forecasts, the all-sky experiment shows statistically significant reductions in root-mean-square error (RMSE) by 1%–2% up to a maximum of 7 days over the tropical region. Moreover, 1-month forecast sensitivity to observation (FSO) experiments demonstrated that both clear-sky and all-sky MWHS-2 radiances can substantially reduce short-range forecast errors, with the all-sky approach increasing the total FSO impact by about 30% relative to clear-sky assimilation.